Beyond Outbreak Counts: A Novel Epidemiological Classification of Major Animal Diseases Using Loss-to-Case and Cases-per-Outbreak Ratios - Kumar*, Arun HS (Biology, Engineering, Medicine and Science Reports, 2026)
The 2026 World Organisation for Animal Health (WOAH) 2nd edition of State of the World’s Animal Health report provides critical insight into the global burden of infectious diseases affecting livestock, poultry, wildlife, and companion animals. While traditional epidemiological indicators such as the number of outbreaks, cases, and deaths remain essential for disease monitoring, they do not fully capture the severity and transmission dynamics associated with different diseases. This report introduces two additional epidemiological indicators: the loss/cases ratio and the cases/outbreaks ratio. The loss/cases ratio evaluates the relative severity and mortality burden of a disease by comparing total animal losses or culling events to confirmed cases, whereas the cases/outbreaks ratio estimates outbreak intensity and transmission scale by measuring the average number of cases per outbreak. Using these parameters, the ten major animal diseases were classified into high-, medium-, and low-impact categories. Sheep pox and goat pox together with Avian influenza in poultry emerged as high-loss diseases due to their exceptionally high mortality and culling burden. Avian influenza in poultry was identified as the only high-outbreak disease, reflecting the extreme transmission intensity associated with intensive poultry production systems. African swine fever, Foot and mouth disease, and Peste des petits ruminants demonstrated moderate outbreak intensity, while diseases such as Rabies and New World screwworm showed comparatively lower outbreak concentration despite wide geographic distribution. The findings demonstrate that integrating these new indicators into animal health surveillance systems can improve disease prioritisation, strengthen risk assessment, and support more targeted prevention and control strategies. This classification framework provides a more comprehensive understanding of disease behaviour and global animal health threats.
Keywords: Animal Diseases; Epidemiology; Outbreak Intensity; Mortality Ratio; Transboundary; Diseases